THE TABUT FESTIVAL OF BENGKULU AS AN IDEA FOR A PAINTING WORK - Anita Sari, Dea; Susanto, Moh. Rusnoto; Cahyono, Nugroho Heri; Dewobroto, Bambang Trisilo (International Journal of Engagement and Empowerment (IJE2), 2024)
Bengkulu is a province in Indonesia. This province also has a tradition that has developed into a highly valued cultural festival called the Ark Festival. This festival was initially held to commemorate the heroic story of the grandson of the Prophet Muhammad PBUH, namely Husein Bin Ali Bin Abi Thalib, who died in battle in Padang Karbela, Iraq. This tradition then continues to develop into a cultural festival, but the value of tradition is still maintained and implemented. The purpose of creating the Bengkulu Ark Festival painting as an idea for creating paintings is to fulfil the desire for expression. In addition, to develop the creativity of ideas and painting techniques. Then, to find a personal style. So that the general public can enjoy the art in the form of paintings. Finally, to create a sense of love for Indonesian culture and to preserve it. In creating the final project, instead of a thesis, the method of creation used is Gustami SP's approach. The three stages of the creation method used are exploration, design, and realization of artworks. This method is appropriate in the process of creating the artwork. The artworks created are all based on the theme of the Bengkulu Ark festival. The primary medium used is canvas, which is the same size as 100 x 100 cm. Up to the realization of the work and accountability, the design process is carried out in a structured manner